ANALISIS RESEPSI KHALAYAK DALAM MEMAKNAI KEKERASAN SEKSUAL BERBASIS ELEKTRONIK (KSBE) PADA FILM LIKE & SHARE - Nieda Nabila, (2024)
This research aims to explore the audience's reception of the film "Like & Share" regarding the issue of electronic-based sexual violence using Stuart Hall's Reception Encoding Decoding theory, focusing on variations in the backgrounds of informants, including differences in perspectives on the age of victims. This research employs a qualitative method utilizing a reception analysis approach, with the film "Like & Share" as the data source and involving five informants who watched the film as the audience. Interviews were conducted with each informant to gain a profound understanding of the reception of the representation of electronic-based sexual violence in the film. Within Stuart Hall's Reception theory framework, the analysis results indicate that all five informants can be categorized into three reception positions, namely the Dominant Hegemony position. All informants agree and support the overall meaning conveyed by the film, depicting electronic-based sexual violence as a serious act that has traumatic impacts and alters the characters of the victims. In detailing their receptions, the first informant, Bu Aida, emphasizes the potential for victims to rise and continue their lives. Hilma, the second informant, highlights the positive treatment of victims in the film and the importance of social support. Iqbal, the third informant, provides a perspective on the vulnerability of victim characters, especially regarding their age. Mas Tariz, in line with the previous informants, focuses on the fatal impact of electronic-based sexual violence. The fifth informant, Widya, emphasizes the importance of realistic portrayal to enable the audience to feel the experiences of the victims. In the overall study, the informants conclude that the film "Like & Share" successfully depicts the logical and realistic impacts of electronic-based sexual violence, providing a profound understanding of the psychological trauma experienced by the characters. This conclusion offers a robust view of the film's success in conveying its message and stimulating the thoughts and empathy of the audience toward this sensitive issue.